2010
DOI: 10.1016/j.margeo.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Active venting sites on the gas-hydrate-bearing Hikurangi Margin, off New Zealand: Diffusive- versus bubble-released methane

Abstract: Keywords: methane seeps ROV Hikurangi Margin sea-floor observations temperature measurements bubble-release activity During the 'New Vents' SO191 cruise in 2007, the activity and distribution of seep sites on the gas-hydratebearing Hikurangi Margin, off northeastern New Zealand, were subjected to a highly detailed interdisciplinary study. Here we report on the visual observations and in situ measurements of physical properties performed with a ROV (remotely operated vehicle) and other video-guided platforms at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…At Faure Site (Fig. 6), CH 4 concentration fluctuations were documented in both the ambient bottom water and the chamber water, which coincide with tidally induced fluctuations of currents and acoustic backscatter flares , where gas seep activity was clearly evident [20]. Reference [34] describe hydro-acoustic bubble flares in the water column and interpret high-amplitude seismic reflections, extending from a shallow BSR towards the seafloor, as preferred gas migration pathways that exploit relatively high sedimentary layers through the gas hydrate stability zone (GHSZ).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…At Faure Site (Fig. 6), CH 4 concentration fluctuations were documented in both the ambient bottom water and the chamber water, which coincide with tidally induced fluctuations of currents and acoustic backscatter flares , where gas seep activity was clearly evident [20]. Reference [34] describe hydro-acoustic bubble flares in the water column and interpret high-amplitude seismic reflections, extending from a shallow BSR towards the seafloor, as preferred gas migration pathways that exploit relatively high sedimentary layers through the gas hydrate stability zone (GHSZ).…”
Section: Discussionmentioning
confidence: 84%
“…Visual inspection of the landers by ROV [20] showed that the deployment sites were indeed in the immediate vicinity of vent holes discharging free gas (Fig. 5), which is clearly reflected in the backscatter data of the uplooking ADCP mounted on FLUFO (Fig.…”
Section: B Lander Deployments At Faure Sitementioning
confidence: 98%
See 2 more Smart Citations
“…In particular, where the SMTZ is close to the seabed, it can support the establishment of a chemosynthesis-based megafauna (Gay et al, 2006;Judd and Hovland, 2007) dominated by mollusks, annelids, and crustaceans (Kiel, 2010). Gas seepage intensity varies over various time scales (Naudts et al, 2010;Ho et al, 2012) as a function of migration mechanisms and pathways, typically faults, hydrofractures, or sand injectites (Mazzini et al, 2003;Duranti and Mazzini, 2005;Jonk et al, 2005;Hurst and Cartwright, 2007;Ho et al, 2016). The Panoche giant injection complex (California) is one of the world's largest sand injection complexes.…”
Section: Introductionmentioning
confidence: 99%